IMPLEMENTATION OF THE MA'NA CUM MAGHZA APPROACH IN UNDERSTANDING WITNESSES OF ADULTERY IN THE QUR'AN - Agusalim Agusalim (Journal of Islamic and Interdisciplinary Research, 2025)
In the testimony of adultery, scholars do not accept women's testimony as witnesses. At this time, women and men have the same opportunities in access to education, social, and so on. Unlike women in ancient times who were ordered to stay at home. Seeing this phenomenon, researchers try to study the witness of adultery contained in Q.S. An-Nūr verse 04 analyzing it using the Ma'na cum maghza approach, namely an approach that emphasizes interpretation based on two main factors, namely the historical meaning/main message (ma'na), and the main message/historical significance (maghza) then the significance of the text is developed into the current context and discipline. The purpose of this study is to re-examine the case of witnesses in adultery cases whether women can be witnesses in adultery cases. The findings in this thesis are: (1) The historical meaning (ma'na at-tarikhi) of Q.S. An-Nūr verse 04. Proving a case of adultery requires 4 male witnesses who saw the case directly. (2) The historical phenomenal significance (maghza at-tarikhi) of Q.S. An-Nūr verse 04 is a warning to society at that time that establishing a case of accusation of adultery is not something trivial, it requires conditions that are difficult to fulfill.